Функціональне забезпечення економічного механізму регулювання виробництва плодово-ягідної продукції - Одношевна, Ольга Олександрівна; Odnoshevnaya, Olga; Губарик, Ольга Миколаївна; Gubaryk, Olga (Миколаївський національний аграрний університет, 2019)
Сучасний розвиток та ефективне регулювання процесу виробництва плодово-ягідної продукції у сучасних реаліях неможливе без розробки та впровадження якісного економічного механізму. Зважаючи на теоретичні аспекти функціонування економічного механізму, зазначимо, що економічний словник висвітлює механізм як послідовність станів процесів, які визначають собою які-небудь дії, явища, систему, пристрій, який визначає порядок якого-небудь виду діяльності. Основною ціллю написання статті є дослідження сутності, складових та функцій економічного механізму регулювання виробництва плодово-ягідної продукції. В результаті дослідження було сформовано та узагальнено теоретичні аспекти функціонування економічного механізму виробництва плодово-ягідної продукції в контексті особливостей його формування. Також було розроблено функціональний механізм виробничого регулювання плодово-ягідної продукції у сучасних умовах. Зважаючи на проведене дослідження, доцільно зазначити, що сучасний стан економічного механізму регулювання виробництва плодово-ягідної продукції відіграє важливу роль у процесу розвитку галузі садівництва. Вважаємо, що представлені рекомендації дозволять оптимізувати процес визначення складових даного механізму та удосконалити його функціональне призначення. Modern development and effective regulation of the process of production of fruit and berry products in modern realities is impossible without the development and implementation of a quality economic mechanism. Given the theoretical aspects of the functioning of the economic mechanism, we note that the economic dictionary highlights the mechanism as a sequence of states of processes, which determine any actions, phenomena, system, device, which determines the order of any kind of activity. Purpose. Метою написання статті є дослідження сутності, складових та функцій економічного механізму регулювання виробництва плодово-ягідної продукції. Results. As a result of the study, theoretical aspects of the functioning of the economic mechanism of production of fruit and berry produce in the context of the peculiarities of its formation were generalized and generalized. A functional mechanism for the production control of fruit and berry products in modern conditions was also developed. The next stage in the study of the economic mechanism's regulation process is to analyze its existing components and develop updated ones. In order to intensify the innovation activity of gardening enterprises in modern conditions, the necessary component is the study of principles and features, which is one of the priority scientific tasks. Organizational and economic mechanism of innovation activity of enterprises, as well as any other mechanism, should be based on a set of principles, which would be expedient to form it at domestic industrial enterprises. According to leading scholars, it is very important to achieve an ease of approach that would ensure the ability to apply these principles for practical purposes, as leaders of domestic industrial enterprises need simplified approaches to solving complex and multidimensional problems. Conclusions. Given the study, it is useful to generalize that the current state of the economic mechanism of regulation of the production of fruit and berry produce plays an important role in the development of the gardening industry. We believe that the presented recommendations will optimize the definition process.
Functional provision of the economic mechanism for the regulation of the production of fruit and berry products
Одношевна О. О., ORCID ID: 0000-0003-4244-0031 Губарик О. М., ORCID ID: 0000-0002-3296-2074
Keywords: економічний механізм; economic mechanism; плодово-ягідна продукція; fruit and berry products; функції економічного механізму; functions of the economic mechanism; складові економічного механізму; components of the economic mechanism.